Implementasi P5 Tema Kearifan Lokal dalam Meningkatkan Kreativitas Peserta Didik pada Pengelolaan Kupang: Implementation of P5 Local Wisdom Theme in Increasing Student Creativity in Kupang Management - Silvia Wanda Agustin; Fita Afifatur Rosidah; Lusi Afritrianita Agtha Isnandar (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2024)
The implementation of the P5 project with the theme of local wisdom carried out at MTs Roudlotul Banat aims to determine the description of the implementation of P5 in improving student creativity and identifying factors that influence the success of P5 implementation. The method used is descriptive qualitative, with data collection through observation, interviews, and document review. The results obtained from the observation show that there is interaction between teachers and students, teacher participation in activities, teacher readiness as a facilitator, mature P5 project planning and evaluation, and a comfortable place for activities. In addition, the results of observations on student creativity get a good predicate, or there is a level of creativity in managing Kupang; this level of creativity occurs because students are active in participating in P5 project activities; in addition, students are able to capture information about the culture and regional specialties, students are also able to mix other ingredients with Kupang ingredients to create new recipes that have never been tried before. In addition to the improvement, the implementation of the P5 project also has several success factors, namely the complete support factor from the school, the availability of adequate resources, and, most importantly, the reciprocal relationship between students and teachers. Thus, the implementation of the P5 project on the theme of local wisdom can affect the level of creativity of students in managing Kupang; in addition, students can also increase their insight and pride in the culture and regional specialties.